Review: A riveting media chronicle of giving voice to the voiceless - Daya Kishan Thussu (Asia Pacific Network, 2014)
Review of: Don’t Spoil My Beautiful Face: Media, Mayhem and Human Rights in the Pacific, by David Robie. Foreword by Kalafi Moala. Auckland: Little Island Press in association with the Pacific Media Centre. 2014, 362 pp. ISBN 978-1877484-25-4